Liquid Biopsy in Colorectal Carcinoma: Clinical Applications and Challenges - Kolenčík, Drahomír; Shishido, Stephanie N; Pitule, Pavel; Mason, Jeremy; Hicks, James; Kuhn, Peter (Cancers, 2020)
Colorectal carcinoma (CRC) is characterized by wide intratumor heterogeneity with general genomic instability and there is a need for improved diagnostic, prognostic, and therapeutic tools. The liquid biopsy provides a noninvasive route of sample collection for analysis of circulating tumor cells (CTCs) and genomic material, including cell-free DNA (cfDNA), as a complementary biopsy to the solid tumor tissue. The solid biopsy is critical for molecular characterization and diagnosis at the time of collection. The liquid biopsy has the advantage of longitudinal molecular characterization of the disease, which is crucial for precision medicine and patient-oriented treatment. In this review, we provide an overview of CRC and the different methodologies for the detection of CTCs and cfDNA, followed by a discussion on the potential clinical utility of the liquid biopsy in CRC patient care, and lastly, current challenges in the field.
Keywords: CTC; circulating free DNA; circulating tumor DNA; liquid biopsy; colorectal carcinoma; circulating tumor cell; CRC; precision medicine; ctDNA; cfDNA